SARS-COV-2 RNA vaccine compositions and methods of use - BERGLUND LARS PETER AXEL; ARCHER JACOB FREEMAN; REED STEVEN GREGORY; CARTER DARRICK ALBERT; KAMDAR AMIT PRAVL; ERASMUS, JESSE; DUSSEY, MALCOLM, S; BERUBE, BRIAN (2024)
The present disclosure provides compositions, methods of treatment, and methods of making and using the compositions to deliver nucleic acids to a subject. The compositions described herein comprise a lipid carrier, optionally comprising inorganic particles capable of being mixed with a nucleic acid. Also provided are methods of using the compositions as COVID-19 vaccines for the treatment of coronavirus infections. 本公开内容提供了组合物、治疗方法以及制备并使用组合物以将核酸递送至受试者的方法。本文描述的组合物包含脂质载体，任选地包含能够与核酸混合的无机颗粒。还提供了使用该组合物作为COVID-19疫苗用于治疗冠状病毒感染的方法。